Convection patterns gradients of non-living and living micro-entities in hydrogels. (December 2020) - Canadas, Raphaël F.; Patrício, Pedro; Brancato, Virginia; Gasperini, Luca; Caballero, David; Pires, Ricardo A.; Costa, João B.; Pereira, Hélder; Yong, Ping; da Silva, Lucília P.; Chen, Jie; Kundu, Subhas C.; et al.
Abstract : Inducing thermal gradients in two injected fluid systems results in the temporal formation of mixing conductive streams. If preserved through sol-gel transition, this mechanism can be used to drive and pattern non-living and living entities in mixed hydrogels. Interfaces are vital in nature, where gradients of non-living and living entities build distinct yet continuous integrated living tissues. However, the common tissue fabrication methodologies often result in dissimilar interfaces, lacking continuity through the interfaced engineered tissues. Thus, there is an urgent need for the fabrication of heterotypic but continuous engineered tissues with spatial control over biomimetic features. Here, we demonstrate the influence of gel injection temperature on the patterning of gradients of non-living and living entities. The experimental part was confirmed by numerical modelling, showing the formation of convective lines which spatially drive microscale microparticle and cells when different temperatures are applied in the sequential injection of two gels. Based on this finding, pure gellan gum (GG) and blended GG with methacrylated gelatin (GelMA) systems were used to program the formation of gradient features in hydrogels, such as microparticle and cells distribution patterns, polymeric bioactivity, degradation, controlled release, and stiffness. The correlation between gel injection temperature and gradients formation can be applied to tissue interface modelling, regeneration, drug release systems, and broader materials engineering fields. Graphical abstract: Image, graphical abstract